Estudo retrospectivo das causas de surdez em crianças de 0 a 12 anos atendidas em instituição especializada - Swensson, Rubem Cruz (2009)
Objective: Study the occurrence of infectious and contagious diseases in deafness children between 0 to 12 years old attended in a nongovernmental organization at Sorocaba city on the years 1995 and 2005. Method: This is a research based on retrospective study using database of an institution specialized on care of deafness people at Sorocaba city, São Paulo state. Were analyzed archives of children between zero to 12 years old on the years 1995 and 2005. Results: Of the 339 charts of patients between 0 and 15 years old attended the institution, were selected in 1995 and 2005, respectively, 70 and 155 children. In both years the cause of deafness was unknown in most children. Among the known causes, the most prevalent was the post-neonatal meningitis (24.0%) followed by congenital rubeola (11.1%). Although had not been statistically significant compared to the year 1995 and 2005, it was a decrease by 4.6% (from 14.3% to 9.7%) in prevalence of congenital rubeola. Was not observed any cases of neonatal herpes, HIV / AIDS or neonatal meningitis. Diseases such as congenital rubeola and meningitis decreased their prevalence rates in 2005 but toxoplasmosis and cytomegalovirus continued to occur. It´s possible observe a decrease of cases of children with late deafness (acquired) in 2005. This decrease may be due to vaccination campaigns against some etiologic agents especially the Haemophilus influenza type b, which became part of the portfolio of vaccine in 1999. Conclusions: Although the research conducted at the institution was not statistically significant, comparing the years 1995 and 2005, were find decreased by 4.6% (from 14.3% to 9.7%) in the prevalence of congenital rubeola, congenital syphilis, cytomegalovirus, and bacterial meningitis. The high number of unknown causes and late referrals emphasizes the need for adequate knowledge of the diagnosis and conduct in relation with hearing loss. Emphasize the professionals in the medical , fonoaudiologica and education fields, the importance of prevention and appropriate treatment of infectious and contagious diseases during pregnancy and postpartum. Disseminate the importance of vaccines, which play an important role to reduce or annul the hearing and neurological sequelae in relation to infectious and contagious disease. Warn the pregnant woman not to eat raw vegetables and raw or rare meat during the pregnancy to avoid toxoplasmosis. Be careful with sex partners due to syphilis and AIDS. Doing the appropriate medical or surgical treatment of diseases of the ear to prevent sequelae. Disclose to health professionals, educators, family, population, the referral to specialist services any suspected change in the hearing of the child especially in the first months of life